Flow cytometric analysis of myelodysplasia: Pre‐analytical and technical issues—Recommendations from the European LeukemiaNet. Issue 1 (11th December 2021) - van der Velden, Vincent H. J.; Preijers, Frank; Johansson, Ulrika; Westers, Theresia M.; Dunlop, Alan; Porwit, Anna; Béné, Marie C.; Valent, Peter; te Marvelde, Jeroen; Wagner‐Ballon, Orianne; Oelschlaegel, Uta; Saft, Leonie; et al.
Abstract: Background: Flow cytometry (FCM) aids the diagnosis and prognostic stratification of patients with suspected or confirmed myelodysplastic syndrome (MDS). Over the past few years, significant progress has been made in the FCM field concerning technical issues (including software and hardware) and pre‐analytical procedures. Methods: Recommendations are made based on the data and expert discussions generated from 13 yearly meetings of the European LeukemiaNet international MDS Flow working group. Results: We report here on the experiences and recommendations concerning (1) the optimal methods of sample processing and handling, (2) antibody panels and fluorochromes, and (3) current hardware technologies. Conclusions: These recommendations will support and facilitate the appropriate application of FCM assays in the diagnostic workup of MDS patients. Further standardization and harmonization will be required to integrate FCM in MDS diagnostic evaluations in daily practice.